NDRG2 regulates the formation of reactive astrocyte-derived progenitor cells via Notch signaling pathway after brain traumatic injury in rats - Zhang, Qinjun; Shi, Rui; Hao, Minghua; Feng, Dongyun; Wu, Rui; Shi, Ming (Frontiers in Molecular Neuroscience, 2023)
In response to traumatic brain injury, a subpopulation of cortical astrocytes is activated, resulting in acquisition of stem cell properties, known as reactive astrocytes-derived progenitor cells (Rad-PCs). However, the underlying mechanisms remain largely unknown during this process. In this study, we examined the role of N-myc downstream-regulated gene 2 (NDRG2), a differentiation- and stress-associated molecule, in Rad-PCs after cortical stab injury in adult rats. Immunohistochemical analysis showed that in the cerebral cortex of normal adult rats, NDRG2 was exclusively expressed in astrocytes. After liu cortical injury, the expression of NDRG2 was significantly elevated around the wound and most cells expressing NDRG2 also expressed GFAP, a reactive astrocyte marker. Importantly, NDRG2-expressing cells were co-labeled with Nestin, a marker for neural stem cells, some of which also expressed cell proliferation marker Ki67. Overexpression of NDRG2 further increased the number of NDRG2/Nestin double-labeling cells around the lesion. In contrast, shRNA knockdown of NDRG2 decreased the number of NDRG2+/Nestin+ cells. Intracerebroventricular administration of stab-injured rats with a Notch antagonist, DAPT, led to a significant decrease in Nestin+/NDRG2+ cells around the injured boundary, but did not affect NDRG2+ cells. Moreover, overexpression or knockdown of NDRG2 led to up- and down-regulation of the expression of Notch intracellular domain NICD and Notch target gene Hes1, respectively. Taken together, these results suggest that NDRG2 may play a role in controlling the formation of Rad-PCs in the cerebral cortex of adult rats following traumatic injury, and that Notch signaling pathway plays a key role in this process.